Exercising No Harm Rule: Claims for Damage and Loss Due Climate Change Effects - Mada Apriandi Zuhir; Febrian Febrian; Murzal Murzal; Ridwan Ridwan (Sriwijaya Law Review)
The act of utilising all the resources owned by a state, including natural resources, is the right of every state. However, its use is prohibited if it causes harm to other states. This is then referred to as the principle of no harm rule in international law. Therefore, each state is responsible not for causing damage to other States' environments or areas outside the limits of its jurisdiction. This article will analyse the development of the no harm rules and its application model for claiming state responsibility. As normative research, it used secondary data as the main data, and the primary, secondary and tertiary legal materials were analysed qualitatively. In discussion, this principle has long existed as customary international law to mitigate transboundary pollution. In the case of the environment in general, many studies have applied this principle. However, due to the uniqueness of the climate change issue, evidence and proof of the impacts caused cannot be used as the basis for a lawsuit like ordinary environmental cases. Based on the discussion and simulation conducted, it is concluded that the no harm rules principle can be applied to climate change issues. However, this principle is not satisfactory and has limitations in its application.